The Caucasus - Forsyth, James, 1928- (New York ; Cambridge)
xviii, 898 s., [24] s. resim
Keywords: "A fascinating new survey of the Caucasus which provides a unified narrative history of this complex and turbulent region at the borderlands of Europe, Asia and the Middle East, from prehistory to the present. For thousands of years the Caucasus has formed a hub of intersecting routes of migration, invasion, trade and culture and a geographical bridge between Europe and Asia, subject to recurring imperial invasion. Drawing on sources in English, Russian and translations from Persian and Arabic, this authoritative study centres on the region's indigenous peoples, including Abkhazians, Armenians, Azerbaijanis, Chechens, Daghestanis, Circassians, and Georgians, and their relations with outsiders who still play a part in the life of the region today. The book presents a critical view of the role of Russian imperialism in the Caucasian countries and the desperate struggle of most of its native peoples in their efforts to establish a precarious independence." --